Woman's Voice Speaks Out for Gender and The Environment in Gadis Pesisir - Agustina Hiqma Nur (EDP Sciences, 2021)
The life of women in Indonesia’s coastal areas tends to have limitations in accessing education. They are a minority group who often have to stay at home and do domestic work. The purpose of this paper is to explore the environmental issue, ecological, mixed with feminist criticism in Gadis Pesisir, a short story by Zainul Muttaqin. By defining the woman's minimum role in studying at the college and her desire to develop the coastal society, the author exposes the contrast between them, related to the coastal welfare and cultural conflicts between the gender relation and the spirit to advance the community. This research is a descriptive qualitative method that uses library research. Ecocriticism and feminist criticism are highlighting the interaction among literary text, nature, and women's voices. By raising this local issue, the writer described the women empowerment loss of patriarchy culture. This short story perpetuates the powerlessness of coastal women in fighting patriarchal culture, stigma, and the marine environment. They can only dream and wait for a miracle to change their destiny. It is contrary to women's rights which are fought for by feminists on the equality of women and men in accessing education, obtaining job opportunities, and careers in various fields.